1975
DOI: 10.1086/181732
|View full text |Cite
|
Sign up to set email alerts
|

A search for VHF radio pulses in coincidence with celestial gamma-ray bursts

Abstract: A detailed search for coincident pulses has been made of VHF radio recordings taken at widely spaced stations around the times of 19 celestial '")'-ray bursts between 1970 and 1973. No coincident pulses were found above a sensitivity level of the order of 10-12 ergs cm-2 (event)-1 in a 1-MHz bandwidth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
2
11
0
Order By: Relevance
“…In 1 second of observations, COBE has the following sensitivities: 26.4, 28.8 and 98.6 KJy for, respectively, the 31, 53 and 90 GHz channel. This sensitivities are of the same order or magnitude of the two similar high sky coverage searches by Baird et al, 1975 andInzani et al, 1982. Given these noise levels, the best use of COBE data is for studying delayed or anticipated emission on long observing times where the noise can be reduced by integration to a useful level. The COBE data has also been used to put upper limits on prompt emission which would be coincident with the GRB event (see Bontekoe et al 1995).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…In 1 second of observations, COBE has the following sensitivities: 26.4, 28.8 and 98.6 KJy for, respectively, the 31, 53 and 90 GHz channel. This sensitivities are of the same order or magnitude of the two similar high sky coverage searches by Baird et al, 1975 andInzani et al, 1982. Given these noise levels, the best use of COBE data is for studying delayed or anticipated emission on long observing times where the noise can be reduced by integration to a useful level. The COBE data has also been used to put upper limits on prompt emission which would be coincident with the GRB event (see Bontekoe et al 1995).…”
Section: Introductionsupporting
confidence: 73%
“…The previous cited works were concentrated on studying the delayed emission of single GRB events. Two works (Inzani et al, 1982 andBaird et al, 1975) have been published so far about an extended sky search on radio-counterpart similar to the work presented in this paper.…”
Section: Introductionsupporting
confidence: 57%
“…Finally, we to note that including the other previous lowfrequency experiments, Baird et al (1975), Benz &Paesold (1998), andBalsano (1999), in the analysis makes no difference to the results.…”
Section: Detection Statisticsmentioning
confidence: 81%
“…Baird et al (1975) observed 19 GRB events at 151 MHz between 1970 and 1973, with a time resolution of 0.3 s; they searched for coincident radio pulses with two or more stations over periods −1 hr to +10 hr relative to the GRB event times. Their search failed to locate any astronomical radio pulse above their sensitivity limit of 10 5 Jy.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many searches for prompt, coherent radio counterparts to GRBs to date, but none have yielded detections thus far(e.g., Baird et al 1975;Inzani et al 1982;Koranyi et al 1995;Dessenne et al 1996;Benz & Paesold 1998;Balsano 1999;Bannister et al 2012, see Granot & van der Horst 2014 for brief summary). Most recently, Obenberger et al (2014) searched for ≡δ Notes.…”
Section: Introductionmentioning
confidence: 99%